Seminal plasma PGK2 serves as a predictive biomarker for post-varicocelectomy sperm motility improvement in varicocele subjects - Yang, Cheng; Li, Jianxiong; Wu, Shenghao; Liu, Cundong; Zhou, Ranran; Zhao, Shan-Chao (Translational andrology and urology, 2025)
Not all varicocele (VC) patients experience improvements in semen quality after undergoing varicocelectomy. This study aims to investigate whether phosphoglycerate kinase 2 (PGK2) protein in seminal plasma could serve as a predictive biomarker for the enhancement of sperm motility post-varicocelectomy. Sixty patients diagnosed with VC-associated asthenospermia and who underwent varicocelectomy at the Third Affiliated Hospital of Southern Medical University were included in this study. Semen samples from 33 healthy donors were also collected. Hematological and semen analysis parameters were assessed at baseline and at the 6-month postoperative follow-up. The concentration of PGK2 in seminal plasma was determined using enzyme-linked immunosorbent assay (ELISA). Additionally, eleven machine learning algorithms were employed to develop a model to evaluate the effectiveness of varicocelectomy based on PGK2 concentration, hematological parameters, and semen quality indicators. The levels of PGK2 in seminal plasma were significantly lower in VC patients compared to healthy donors (P<0.001). Increased levels of PGK2 were observed in the VC subjects after the varicocelectomy (P<0.001). PGK2 concentration was found to be a significant indicator [area under curve (AUC) =0.735, 95% confidence interval (CI): 0.601-0.860] and an independent predictor (P=0.003, P=0.049) of the success of varicocelectomy. The linear discriminant analysis (LDA) model demonstrated strong classification ability for assessing varicocelectomy outcomes in both the training (AUC =1.000, 95% CI: 1.000-1.000) and testing (AUC =0.804, 95% CI: 0.619-0.963) groups. PGK2 in seminal plasma shows promise as a potential biomarker for predicting improved sperm motility following varicocelectomy, thus aiding in clinical decision-making regarding therapeutic approaches.